Critical internet literacies : reconsidering creativity, content, and safety online - Cohen, Jamie, 1981- (New York, NY : Routledge, 2025)
"An introductory critical internet studies text that builds upon media literacy and digital culture theory to offer a thorough examination of the intersection of online technology and culture. We are now collectively at a hinge point in the evolution of the web where online influencers can sway national discourse, geopolitical events are remixed through memes, and online harms are misunderstood. This book argues that people are generally aware that online media has repercussions in off-platform spaces, but sometimes lack the language to properly critique online trends, memes, and internet-born media. How are citizens, activists, and marginalized groups able to use these tools effectively and safely in these times? Jamie Cohen explores aspects of internet culture in an approachable manner, building upon critical media literacy and applying a critical techno-cultural analysis as a methodology to reimagine how media literacy can operate in an online media environment. The book explores key topics such as accessibility, the creator economy, content moderation, tech bias, platform capitalism, internet culture, and safety. Offering a new way of reading internet media and critiquing content and creators, this book is essential reading for students and scholars of digital culture, internet culture, media literacy, social media, and beyond"--
Critical perspectives on digital cultures -- The creator economy and the hyper-niche -- Memes and visual communication -- The online to mainstream media pipeline -- The "social dilemma" dilemma : critiquing awareness media -- The moderated internet : reconsidering safety online -- Creating content with accessibility -- Building resilient online communities.
Keywords: Media literacy; Internet literacy; Internet -- Social aspects; Social media and society; Mass media and culture